Psoriasis and infection. A clinical practice narrative. (5th August 2018) - Rademaker, Marius; Agnew, Karen; Anagnostou, Nicholas; Andrews, Megan; Armour, Katherine; Baker, Christopher; Foley, Peter; Gebauer, Kurt; Gupta, Monisha; Marshman, Gillian; Rubel, Diana; Sullivan, John; et al.
Abstract: The Australasian Psoriasis Collaboration has developed a clinical practice narrative with respect to the relationship between psoriasis, its treatment and infection. The cutaneous microbiome of patients with psoriasis is different to those without psoriasis, although the significance of this is unclear. Whilst a wide range of microorganisms has been associated with psoriasis (including β‐haemolytic streptococci, Staphylococcus aureus, Porphyromonas gingivalis, Candida albicans, Chlamydia psittaci, human immunodeficiency virus and hepatitis C virus), there is limited evidence that antimicrobial therapy is of direct benefit in preventing flares of psoriasis. Psoriasis is independently associated with an increased risk of serious infection, but the absolute risk is low. The risk of serious infections is further increased with immune‐modulatory treatments. The decision whether to, and when to, stop or resume immune‐modulatory treatment after a serious infection has occurred depends on risk assessment for that patient, taking into account the infection being treated, the risk of recurrent infection, any interventions that can modify the risk and the need for psoriasis control. Live vaccines (e.g. MMR, varicella, zoster and yellow fever) are generally contraindicated in patients with psoriasis on immune‐modulatory agents, but this depends on the degree of immune suppression and individual risk factors. Wound healing in psoriasis is normal. Treatment with infliximab, adalimumab, etanercept, methotrexate and ciclosporin can safely be continued through low‐risk surgical procedures. For moderate‐ and high‐risk surgeries, a case‐by‐case approach should be taken based on the patient's individual risk factors and comorbidities.